PELAKSANAAN PEMENUHAN HAK NARAPIDANA UNTUK MENDAPATKAN PEMBINAAN KEMANDIRIAN DAN KETERAMPILAN DI LEMBAGA PEMASYARAKATAN KELAS III SULIKI - Miftahul Jannah; Sukmareni Sukmareni; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Correctional Institutions is a place to provide guidance to Prisoners and Correctional Students. Article 2 of Government Regulation number 31 of 1999 concerning the Guidance and Guidance of Correctional Assisted Citizens explains that the coaching and coaching activity program includes personality and independence coaching and development. Prisoners will receive guidance on independence and skills to equip them when they return to society. Regarding the implementation of independence and skills development, there are several obstacles faced by the Correctional Institutions Suliki Class III Penitentiary. This research is normative and empirical legal research, namely research that refers to legal norms contained in statutory regulations, literature, existing legal norms and data obtained from document studies and interviews at Class III Prison Suliki and then analyzed to answer community problems in this study related to the implementation of rights fulfillment to obtain independence and skill development. The results of the study show that the implementation of fulfilling the rights of convicts to gain independence and skills training has been going well, but there are still some obstacles. Prison Suliki has made several efforts to overcome obstacles in the implementation of independence and skills in Prison Suliki, but the efforts made are still not optimal due to budget constraints.